Modeling of optimal green liquor pretreatment for enhanced biomass saccharification and delignification by distinct alteration of wall polymer features and biomass porosity in Miscanthus. (October 2020) - Alam, Aftab; Wang, Youmei; Liu, Fei; Kang, Heng; Tang, Shang-wen; Wang, Yanting; Cai, Qiuming; Wang, Hailang; Peng, Hao; Li, Qian; Zeng, Yajun; Tu, Yuanyuan; et al.
Abstract: Miscanthus is a leading bioenergy crop with enormous biomass resource convertible into bioethanol and biochemicals. However, lignocellulose recalcitrance basically causes costly bioethanol production with potential secondary pollution to the environment. In this study, the green liquor (mixed sodium carbonate and sodium sulfide) pretreatments were optimized using response surface methodological modeling for enhancing biomass saccharification and delignification in Miscanthus. By comparison, the optimal saccharification approach led to relatively higher hexose yield of 87% (% cellulose) for bioethanol yield of 17.1% (% dry matter) with the sugar-ethanol conversion rate at 98%, whereas the optimal delignification approach could achieve the highest delignification rate at 93% potential for lignin-derived biofuel or value-added biochemicals. Notably, those two optimized pretreatments could distinctively extract hemicellulose-lignin complex and altered wall polymer features, leading to much increased cellulose accessibility for efficient biomass enzymatic hydrolysis. Exceptionally, the optimal delignification led to decreased biomass porosity accountable for relatively lower hexose yield, suggesting that its cellulose microfibrils may be aggregated from excessive non-cellulosic polymers extraction. Hence, this study has demonstrated two optional strategies for green-like and cost-effective biofuels and biochemical production in Miscanthus and other bioenergy crops. Graphical abstract: Image 1 Highlights: Green liquor pretreatment was optimized for saccharification and delignification. Optimal saccharification approach led to higher hexose yield at 87% (% cellulose). The highest delignification rate was so far obtained at 93% for advanced biofuels. Two pretreatments distinctively altered wall polymer features and inter-linkages. Two optional strategies for green-like biofuel production in bioenergy Miscanthus.